Effectiveness of Abdominal Effleurage Massage Training in Improving Adolescent Girls' Knowledge and Skills to Manage Dysmenorrhoea - Kadek Sri Ayuningsih; Purnamayanti , Ni Made Dwi; Utarini , Gusti Ayu Eka; Tirtawati, Gusti Ayu (Viva Medika, 2025)
Dysmenorrhea is menstrual pain that interferes with adolescent activity in the learning process. Providing health education about dysmenorrhea is very important to reduce the impact of discomfort caused by dysmenorrhea. Dysmenorrhea also has a psychological impact in the form of emotional conflict, tension, and anxiety. The purpose of this study was to determine the differences in knowledge and skills of adolescent girls before and after abdominal effleurage massage training to overcome dysmenorrhea in Banjar Laing, Pandak Village. Research method Pre-Experimental Pre-Post Test One Group Design. The implementation of the research in April 2024 with total sampling technique. The sample number was 45 young women in Banjar Laing, Pandak Village. Data collection by conducting pretest and posttest. Data analysis using the Wilcoxon test with a meaning level of p < 0.05. The results there is a significant difference in the level of knowledge and skills before and after abdominal effleurage massage training to overcome dysmenorrhea with p values of 0.000 < α 0.05. This study can be concluded that abdominal effleurage massage training improves knowledge and skills of young women in Banjar Laing, Pandak Village, Bandung, Tabanan. Abdominal effleurage massage training is conducted to increase the independence of young women in overcoming dysmenorrhea.